STRATEGI KOMUNIKASI CROWDFUNDING PADA KOLASE.COM - Venessa Agusta Gogali; Fajar Muharam; Syarif Fitri (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
Crowdfunding is a new method in fundraising activities based online. Moreover, the level of penetration of social media to the community is increasingly high. This makes social activists and academics realize that it is important to study social media communication strategies in crowdfunding activities. There is encouragement to provide an overview of crowdfunding activities. So the author conducted a research on "Crowdfunding Communication Strategy Through Kolase.com Through Case Study on the #BikinNyata Program Through the Kolase.com Website that successfully achieved the target. Keywords: Strategic of Communication, Crowdfunding, Social Media.